Evaluating the social sustainability of urban regeneration initiative in Malaysia : the case of Kuala Lumpur Sentral, Brickfields - Nik Hazwani Nik Hashim; Anuar Alias; Melasutra Md. Dali (Penerbit Universiti Kebangsaan Malaysia, 2021)
Urban regeneration is deemed as an applicable approach in resolving the intricate problems encountered in run-down old cities via numerous initiatives toward the improvement of physical, economic, social, and environmental conditions. Generally, urban regeneration supports sustainable development as it utilizes the already developed land. Nevertheless, implementing this approach poses some setbacks because often the focus is more on accomplishing economic regeneration while overlooking the implications on social and environmental sustainability. This paper aims to investigate the issue in the local context, by evaluating the impacts of urban regeneration initiative implemented in Kuala Lumpur, Malaysia. Certain social sustainability indicators are examined through questionnaire survey conducted to the 400 residents living within 2 km vicinity of Kuala Lumpur (KL) Sentral which is one of the urban regeneration initiatives done in Brickfields, Kuala Lumpur. The resulted analysis indicated there are positive impacts in few indicators following urban regeneration, such as the provision of community benefits as well as the improved living environment. Nonetheless, the implications are inconsequential for other indicators, signifying the needs for a comprehensive method that concentrates more on improving the quality of life for residents living in run-down old cities. This study contributes to the advancement of knowledge in urban regeneration studies in Malaysia by demonstrating that further efforts are crucial to improve the social sustainbaility performance of urban regeneration initiative by integrating the fundamental determinants within the policy framework.